Studying Effectiveness in International Relations : a guide for students and scholars. - Hegemann, Hendrik (Verlag Barbara Budrich, 2012)
The question of how effective political tools actually are is among the most hotly debated in contemporary IR theory. There is no unanimity how to even measure the effectiveness and impact different political measures produce. This book comprehensively introduces social science students and scholars to the various fields of effectiveness and impact research in the study of international relations.
International Socialization: From Studying Effectiveness to More Effective Studies?
Keywords: International relations.; World politics.; Relations internationales.; Politique mondiale.; international relations.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; POLITICAL SCIENCE / International Relations / General; International relations; World politics